PENDAMPINGAN EVALUASI INSTING TAHAP PERENCANAAN INSPEKTORAT DAERAH KABUPATEN KLATEN - Zeta, Vania Miranda; Jati, Agung Nugroho; Utami, Tri; Nugrahani, Cahaya; Prasetyo, Jarot; Nugroho, Arif Julianto Sri; Setyawanti, Dandang (LPPM Universitas Widya Dharma Klaten, 2023)
These activities try to identify the most important dimension and to examine the level of service quality with Servqual model, expectation and perception of external people towards the Training Insting Perangkat Desa Kabupaten Klaten 52 respondents as samples. In performing this policy, there is many problems both technical and operational. The research illustrates that the Servqual model as a useful managerial tool can be applied in identifying areas to which management resources should be allocated in order to improve and enhance the quality of service the Diklat Insting. Finally, these external customers have the highest expectation on tangible of the Insting Inspektorat Daerah Klaten service.